Analysis of Dental Health Service Satisfaction in Dental Polyclinic Patients : A Cross-sectional Study - Peniza Suliati; Nani Sari Murni; Chairil Zaman; Yusnilasari Yusnilasari; Bebbi Arisya Kesumaputri (School of Health Sciences Al-Ma'arif, 2025)
Patient satisfaction is an important indicator in assessing the quality of healthcare services, including dental care services. Tugu Jaya Hospital in OKI Regency has not yet obtained evaluative data regarding patient satisfaction in its dental outpatient services. This study aims to determine the relationship between respondent characteristics and service quality dimensions with patient satisfaction. The study employed a quantitative design with a cross-sectional approach and involved 70 respondents selected through purposive sampling. Data were analyzed using chi-square tests and multiple logistic regression. The results showed significant relationships between education (p = 0.001; PR = 0.281), tangible (p = 0.000; PR = 7.059), empathy (p = 0.006; PR = 2.819), assurance (p = 0.010; PR = 2.596), and reliability (p = 0.022; PR = 2.338) with patient satisfaction. Meanwhile, no significant relationships were found between age (p = 1.00), gender (p = 0.495), and responsiveness (p = 0.070) and satisfaction. Among all the variables, the empathy dimension was the most dominant factor influencing satisfaction (OR = 0.208). Patient satisfaction with dental health services is influenced by education and service quality dimensions, particularly staff empathy. Enhancing service quality through empathy and interpersonal communication is the primary recommendation.